ACTN2 (rs6656267) and MPPED2 (rs11031093 and rs536007) polymorphisms in primary dentition caries: A case‐control study. Issue 4 (25th February 2020) - Katifelis, Hector; Sioziou, Anna; Gazouli, Maria; Emmanouil, Dimitris
Abstract: Background: Dental caries represents one of the most common human diseases which can lead to pulpitis, pain, and tooth loss and can negatively affect growth and well‐being. Although dietary and environmental factors have been extensively studied towards their contribution of the disease, genetic factors that contribute one's susceptibility over caries development remain rather clouded. Aim: To investigate the possible contribution of ACTN2 (rs6656267) and MPPED2 (rs11031093 and rs536007) polymorphisms in primary dentition caries. Design: Samples from children (5‐12 years old) were collected and genotyped for ACTN2 (rs6656267) and MPPED2 (rs11031093 and rs536007) polymorphisms. With regard to dmfs index and socio‐economic status, an association between these polymorphisms and primary dentition caries was investigated. Results: ACTN2 (rs6655267) and MPPED2 (rs536007) are not associated with primary dentition caries. MPPED2 (rs11031093, G Allele) is marginally associated. Conclusions: MPPED2 (rs11031093, G Allele) is marginally associated with caries susceptibility on primary dentition.